Effect of biopsychosocial coaching on improving return to work duration after involvement in commuting road crash - Sahak, Nurrul Hafeezah (2018)
Introduction: For every death due to commuting road crash, at least 20 others sustain injuries. Due to multiple injuries, workers who are involved in commuting road crashes had longer medical leave compared to other types of occupational accidents. Prolonged medical leave could arise due to persistent pain, untreated psychological effects (depression, anxiety and stress) and reduction in health-related quality of life reduce the chances of return to work. Injured workers might have the risk of losing the job skills or job as employer search another healthy worker who manage to perform his pre-injury job task to prevent any loss to the organization. Therefore, it is highly recommended for injured workers to attend rehabilitation session to foster their return to work duration. The aim of this study was to test the effectiveness of a multidisciplinary rehabilitation (biopsychosocial coaching) to improve injured workers return to work duration after involved in commuting road crash. Method: Design: A randomized control trial (RCT) study design. Setting: Selangor and Kuala Lumpur. Participants: Eligible 200 workers who were involved in commuting road crash and agreed to participate in SOCSO RTW Program were identified and invited to be part of this study. They were randomly allocated either to the intervention group (received biopsychosocial coaching and vocational rehabilitation) or the control group (received vocational rehabilitation only). Intervention: Biopsychosocial coaching intervention with the aim to reduce biopsychosocial barriers for recovery in order to fasten return to work duration through work goal, healthy living, and stress and pain management. The biopsychosocial coaching intervention was delivered concurrent to usual care and the average coaching involved three one-hour long sessions. Injured workers were provided with “Restore Workbook” during the commencement of the biopsychosocial coaching intervention. The intervention took place at the rehabilitation centre after injured workers had finished their usual care session with the physiotherapist. Results: A total of 200 injured workers participated in this study, with 86.0% of them were male and 69.0% were blue-collar workers. Intervention group reported seven days earlier (not significantly different) of return to work compared to the control group. Injured workers in the intervention group recorded bigger mean difference in biopsychosocial factors, mental health and health-related quality of life domains between baseline and post-intervention. From the total of seventeen variables in this study, fourteen (pain, function, emotion, coping, confidence, work perception, depression, anxiety, physical functioning, role physical, bodily pain, general health, vitality and social functioning) showed significant difference between the intervention and control group at post-intervention. This study found age, gender, function, confidence, depression, anxiety and stress as factors that could affect injured workers’ return to work duration. Conclusion: Duration of return to work among injured workers could be accelerated through the additional of biopsychosocial coaching in usual care. In addition to that, biopsychosocial coaching also reduced biopsychosocial barriers to recovery, depression, anxiety and stress, as well as increased health-related quality of life.